Efficacy of Native Isolates of Trichoderma sp. against Chickpea Wilt in Southern Telangana Zone of Andhra Pradesh - Suresh, M.; Kumar, C. V. Sameer; Sudhakar, R. (International Journal of Bio-resource and Stress Management, 2023)
Effective native isolates of Trichoderma sp. collected from the roots and rhizosphere of chickpea plants growing in the field along with a commercial formulation were tested for their efficacy in controlling four isolates of Fusarium wilt of chickpea. Effect of these bioagents on seed germination, shoot and root length was also evaluated. Chickpea seeds were treated with potential Trichoderma isolates tested in vitro and planted in pots filled with pre-infected soil having the wilt pathogen isolates under RBD. Data on wilt incidence was collected at 15 days interval upto maturity. Native isolates of T. viride supported higher seed germination followed by isolates of T. harzianum and T. virens compared to untreated control. Trichoderma native isolates also induced highest shoot and root length of chickpea plants against all the four isolates of wilt pathogen compared to untreated control (10-15% increase). The performance of the commercial formulation of T. viride was inferior in comparison with native isolates of T. viride. Wilt incidence was least in seeds treated with native isolate of Trichoderma compared to control (25-45.5% reduction). All the native isolates of Trichoderma were found superior in managing the wilt incidence caused by all the four isolates of Fusarium oxysporum f. sp. ciceris compared to the control as well as commercial formulation.